PENGARUH PUPUK BORON (B) DAN SENG (Zn) TERHADAP LAYU PENTIL DAN BUAH KAKAO (Theobroma cacao L.) YANG DAPAT DIPANEN - Ani Kurniawati; Ade Wachjar; Anita Th. Sinaga (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1998)
The experiment was aimed to study the effect of B and Zn on Cherelle Wilt and cacao production. The experiment was conducted at Rajamandala Plantation from March to September 1997. Randomized Complete Block Design was used in this experiment with two factor and three replications. The first factor was 4 levels concentration of B fertilizer : 0 ppm Borax (BO), 3350 ppm Borax (B1), 6700 ppm Borax (B2), and 10050 ppm Borax (B3). The second factor was 4 levels concentration of Zn fertilizer : 0 ppm ZnSO4 (S0), 1250 ppm ZnSO4 (S0), 2500 ppm ZnSO4 (S0), and 3750 ppm ZnSO4 (S0). The result showed that B fertilizer decrease the cumulative numbers of new cherelle, cherelle wilt, good cherelle, and cacao production. Zn fertilizer did not influence all of the parameters. Interaction of B and Zn fertilizer increase the cumulative number of new cherelle and decrease the cumulative numbers of cherelle wilt.